2021
DOI: 10.1253/circrep.cr-21-0129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Patient Background and Treatment Strategy on Clinical Outcomes After Coronary Intervention for Calcified Nodule Lesions

Abstract: Background: The presence of a calcified nodule (CN) is associated with unfavorable clinical outcomes after percutaneous coronary intervention (PCI). This study clarified the optimal management of CNs by reassessing the PCI strategy in association with patient background characteristics and clinical outcomes. Methods and Results: Among 5,332 consecutive PCI cases managed using intra-coronary imaging, CNs were found in 167 lesions (3.1%). CNs were predominantly located at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…Our data also demonstrated that the lesion location differed between the CN and non‐CN groups. The CN is frequently located in the right coronary artery 5,11,23 . Again, our results are consistent with previous studies 5,11,23 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data also demonstrated that the lesion location differed between the CN and non‐CN groups. The CN is frequently located in the right coronary artery 5,11,23 . Again, our results are consistent with previous studies 5,11,23 …”
Section: Discussionsupporting
confidence: 93%
“…The CN is frequently located in the right coronary artery. 5,11,23 Again, our results are consistent with previous studies. 5,11,23…”
Section: Characteristics Of Cn In Hd Patientssupporting
confidence: 93%
“… 24 Japan Case Control Retrospective Good N/A N/A 74 7 9.5 OCT 17 Nozoe et al. 25 Japan Cohort Retrospective Good 73.1 ± 10.2 120 5332 167 3.1 IVUS 18 Terada et al. 26 Japan Cohort Retrospective Good 80.0 (72.0–83.0) 11 156 15 9.6 OCT 19 Torii et al.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of OCT-CN is associated with a higher incidence of target lesion failure. 4,5,29 Appropriate lesion preparation, including the use of debulking devices, such as rotational atherectomy 30 and/or intravascular lithotripsy, 31 during PCI, may need to be considered. Because optimal stent expansion can be hampered by the presence of CN, stentless strategies, such as the combined use of rotational atherectomy and drug-coated balloon number of patients enrolled in the prospective multicenter registry.…”
Section: Discussionmentioning
confidence: 99%